Stylistic Devices Used in Literature (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article explores the main stylistic devices of creating humorous effect in politicians’ speech. The main types of stylistic devices are explained and examples are provided. The role of literary devices is crucial in creating satire or humor therefore this paper gives some examples of famous politicians who used some linguistic means to create humorous effect in political speeches.